Penggunaan Cakram Gizi untuk Meningkatkan Keterampilan Orang dengan HIV/AIDS Memantau Status Gizi secara Mandiri - Yetti Wira Citerawati SY; Erma Nurjanah Widiastuti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Several factors influence people living with HIV/AIDS (ODHA), and one of them is nutritional status. Malnutrition conditions among people with HIV/AIDS could decrease functional capacity that contributes to immunity malfunction and increases morbidity and mortality. This activity aims to increase knowledge and skills in determining nutritional status independently to improve the quality of life of people living with HIV/AIDS. Activity implementation consists of extension activities and practices using BMI Nutrition Disc. There are two evaluation designs, namely assessing participants’ knowledge and skills. Knowledge was measured using pretest and posttest, and then it will be analyzed using N Gain. Skills are measured using a skill assessment form. Further, skills before and after the practice of using BMI Nutrition Disc are measured. Based on the activities, knowledge with a high category includes 9 people (69.2%), whereas medium and low categories each consists of 2 people (15.4%). If added up, most extension participants (84.6%) have a good understanding of the extension contents provided. As regards the media utilization practice, the participants overall can determine nutritional status using BMI Nutrition Disc. The impact of this activity, that people with HIV AIDS can independently determine their nutritional status using BMI Nutrition Disc.